You play the girl: on Playboy bunnies, Stepford wives, train wrecks, and other mixed messages - Chocano, Carina (Houghton Mifflin Harcourt, 2017)
"Who is "the girl"? Look to movies, TV shows, magazines, and ads and the message is both clear and not: she is a sexed-up sidekick, a princess waiting to be saved, a morally infallible angel with no opinions of her own. She's whatever the hero needs her to be in order to become himself. She's an abstraction, an ideal, a standard, a mercurial phantom. In You Play the Girl, Chocano blends formative personal stories with insightful and emotionally powerful analysis. Moving from Bugs Bunny to Playboy Bunnies, Flashdance to Frozen, the progressive '70s through the backlash '80s, the glib '90s, and the pornified aughts--and at stops in between--she explains how growing up in the shadow of "the girl" taught her to think about herself and the world and what it means to raise a daughter in the face of these contorted reflections. In the tradition of Roxane Gay, Rebecca Solnit, and Susan Sontag, Chocano brilliantly shows that our identities are more fluid than we think, and certainly more complex than anything we see on any kind of screen."--Page 4 of cover.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; com5170; communication; cours; discipline; discours dominant; féminisme pop; histoire et politique; journalisme; premier cycle; périodes historiques; représentation des femme*; sofia; systèmes d'oppressions; thématiques

Femmes, attitudes performatives: aux lisières de la performance et de la danse - Colloque "Femmes, attitudes performatives, aux lisières de la performance et de la danse" (2012 : Vandœuvre-lès-Nancy, France); Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy; Boulbès, Carole; Centre culturel André Malraux de Vandœuvre-lès-Nancy (Collection Nouvelles scènes, 2014)
La place et le rôle des femmes dans l'art et dans le spectacle vivant, entre 1912 et 2012, aux lisières de la performance et de la danse. A l'heure des re-enactements et autres remakes des performances historiques, il semblait important de s'interroger sur la place des femmes dans les avant-gardes des années 1910-1970. Quel regard portons-nous, aujourd'hui, sur les pionnières qui ont profondément modifié la danse et la performance, en Europe et aux Etats-Unis ? Réunis pour la première fois, des historiens, des philosophes, des danseurs et deux chorégraphes ont accepté de faire le point sur leurs recherches. Par-delà les catégories artistiques (danse, performance, action, pantomime, théâtre, music-hall...) et les clivages (théorie / pratique ; forme / fond), ce livre est une invitation à partager leurs questionnements sur le spectacle vivant « au féminin », ses archives et ses références. Femmes, attitudes performatives rassemble dix contributions, une « interview performative » de La Ribot et un entretien sur La Part du rite de Latifa Laâbissi et Isabelle Launay.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artistes féministes; arts; corps; cours; danse; discipline; europe; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire de la danse; performance; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques; états-unis

La transidentité: de l'espace médiatique à l'espace public - Espineira, Karine (Champs visuels, 2008)
C'est à partir de l'opération de Christine Jorgensen en 1952 au Danemark, que le fait qu'un homme puisse devenir une femme, après une intervention chirurgicale, entre dans l'esprit du grand public en raison de sa très forte médiatisation. Les identités trans' sont alors loin de s'affirmer comme telles. Il faudra attendre la fin des années 80 pour assister à l'émergence d'une visibilité prenant une forme revendicative. Entre les deux, la psychiatrisation de l'identité. Grâce à l'Internet, les transidentités ne sont plus isolées les unes des autres et ne rejouent plus la dramatique du changement de sexe comme une individuelle et éternelle première fois. Une mémoire s'élabore, se fixe et génère une culture. Leurs relations à l'information et l'identitaire questionnent tout autant. Cette recherche considère le groupe transidentitaire comme un monde social s'institutionnalisant dans un esprit multidisciplinaire à la lumière des sciences de l'information et de la communication, de la psychosociologie, de la théorie de l'engagement, de l'ethnométhodologie, de la sociologie de la traduction et de la communication instituante. L'analyse du traitement télévisuel de la transidentité, considérée comme expression la plus singulière de l'identité, est-elle susceptible de donner des outils de lectures sur la construction des normes de genre au-delà de la transidentité ?
Keywords: 1900-1999; 1950-1959; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; danemark; discipline; discours dominant; europe; féminisme pop; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques; transféminisme

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques